Pasting and textural properties of mixtures of quinoa (Chenopodium quinoa), kiwicha (Amaranthus caudatus), and tarwi (Lupinus mutabilis) flours in an aqueous system - Vidaurre-Ruiz, Julio (2019)
The aim of this research was to evaluate the interaction effects of quinoa, kiwicha and tarwi flours in pasting properties (peak viscosity, VP; trough viscosity, VM; setback viscosity, VR; final viscosity, VF) and textural properties (firmness, consistency, cohesiveness, viscosity index) of the gels formed in an aqueous system using the experimental approach of mixture design. Ten treatments were formulated, which were composed of 3 individual ingredients, 3 binary mixtures, and 4 ternary mixtures. The results of this research show that the high-water absorption capacity and absence of starch from the tarwi flour significantly affected the viscosity parameters of the pastes, as well as the textural properties of the gels. kiwicha flour had a higher viscosity profile (VP: 1188.5 cP, VM: 932.5 cP, VF: 1194.0 cP, VR: 261.5 cP), than quinoa flour (VP: 147.5 cP, VM: 137.5 cP, VF: 336.5 cP; VR: 189.0 cP), however; non-additive and non-linear effects were observed in pasting and textural properties when these flours were mixed in equal proportions. Pasting properties of mixtures were highly correlated with the textural properties of the gels (r = 0.73-0.92, p<0.05). Due to the special rheological and textural characteristics that the mixtures between quinoa with tarwi or kiwicha with tarwi could have, they would be promising for the development of gluten-free bread products